2021
DOI: 10.1016/j.jaim.2020.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Salacia reticulata, Syzygium cumini, Artocarpus heterophyllus, and Cassia auriculata on controlling the rapid formation of advanced glycation end-products

Abstract: Background The excessive formation of Advanced Glycation End-products (AGEs) by non-enzymatic glycation mediates many health complications in the human body and the formation of AGEs largely accelerated under the hyperglycaemic condition. Objective The prospect of the study to assess the strength of inhibiting the rapid AGE formations in four Ayurvedic medicinal plants, namely; Salacia reticulata (stems), Syzygium cumini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…In ayurvedic and indigenous medicines, this plant is used in the treatment of diabetes and several other conditions [13][14][15][16] and in Sri Lanka, decoctions made out of the root and the stem are used in the traditional formulations [13,16,17]. The anti-diabetic activity of the roots and stems of this plant has been scienti cally validated using in vitro, in vivo, and clinical studies [18][19][20][21][22][23][24]. Nevertheless, only very few studies have shown that bark and root extracts can reduce glycated hemoglobin HbA1c [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In ayurvedic and indigenous medicines, this plant is used in the treatment of diabetes and several other conditions [13][14][15][16] and in Sri Lanka, decoctions made out of the root and the stem are used in the traditional formulations [13,16,17]. The anti-diabetic activity of the roots and stems of this plant has been scienti cally validated using in vitro, in vivo, and clinical studies [18][19][20][21][22][23][24]. Nevertheless, only very few studies have shown that bark and root extracts can reduce glycated hemoglobin HbA1c [18,19].…”
Section: Introductionmentioning
confidence: 99%